Management accounting practices in hotels in Nigeria - Ibrahim, Adeyemo Taiwo (2021)
This study investigates the state of management accounting (MA) in hotels in Nigeria. It analyses the level of adoption and benefits derived from a broad set of traditional and contemporary MA techniques and seeks to ascertain their relevance to the decision making process. The use of the Uniform System of Account for the Lodging Industry (USALI), is also investigated. Finally, the study tries to find if there are any significant differences between MA techniques adopters and non-adopters. This study is motivated by a lack of research on MA in hotels located in Nigeria. Data was collected through a questionnaire comprising mainly closed-ended questions. The findings of the study reveal that USALI adoption rate is quite satisfactory and that the decision to adopt the USALI was made mainly by the financial executive/controller. The main reason reported by non-adopters for rejecting the USALI is the satisfaction with the current accounting system. Traditional MA techniques, such as budgeting for controlling cost, budgeting for coordinating activities of the various parts of the organization and product profitability analysis, were found to be more widely adopted than recently developed MA tools. The results also indicate that the use of MA techniques at hotels is positively associated with hotel size, intensity of competition and cost structure. This study contributes significantly to the literature on the usage of MA techniques by filling a gap in the literature. It also provides invaluable insights on the usage of these tools, which might benefit hotel management, researchers, and others.